Shared body plans of lycophytes inferred from root formation of Lycopodium clavatum - Ito, Yuki; Fujinami, Rieko; Imaichi, Ryoko; Yamada, Toshihiro (Frontiers in Ecology and Evolution, 2022)
Late Silurian to early Devonian lycophytes had prostrate aerial axes, while subordinate organs or subterranean axes were formed around the dichotomies of the axes. The subterranean axes are hypothesized to have evolved into root-bearing axes (rhizophores) and roots in extant Selaginellaceae and Lycopodiaceae, respectively. Consistent with this hypothesis, rhizophores are formed on the dichotomies of shoots in Selaginellaceae. However, it has remained unclear whether roots are borne in the same position in Lycopodiaceae. In addition, roots form endogenously in the stem, but no data are available regarding the tissues in stem from which they arise. In this study, we tracked the root development in the clubmoss, Lycopodium clavatum, based on anatomical sections and 3D reconstructed images. The vascular tissue of the stem is encircled by ground meristem, which supplies cortical cells outwardly by periclinal divisions. A linear parenchymatous tissue is present on the ventral side of vascular cylinder, which we call “ventral tissue” in this study. We found that root primordia are formed endogenously on the ventral side of stem, possibly from the ventral tissue. In addition, roots always initiate at positions close to dichotomies of stem. The root-initiating position supports the suggestion that Lycopodium roots share a body plan with the subterranean organs of the hypothesized ancestry.